Developing Students' Pedagogical Culture in an Integrated Cluster Learning Environment - Muminov Shermuhammad Karimovich (Zien Journals, 2022)
This article is aimed at developing the pedagogical culture of students in the context of integrated cluster education, increasing the effectiveness of integrated lessons and teaching principles.
Keywords: pedagogical system; theoretical and practical; coordination; blocking